A randomized trial of high‐dairy‐protein, variable‐carbohydrate diets and exercise on body composition in adults with obesity. Issue 5 (2nd March 2016) - Parr, Evelyn B.; Coffey, Vernon G.; Cato, Louise E.; Phillips, Stuart M.; Burke, Louise M.; Hawley, John A.
Abstract : Objective: This study determined the effects of 16‐week high‐dairy‐protein, variable‐carbohydrate (CHO) diets and exercise training (EXT) on body composition in men and women with overweight/obesity. Methods: One hundred and eleven participants (age 47 ± 6 years, body mass 90.9 ± 11.7 kg, BMI 33 ± 4 kg/m 2, values mean ± SD) were randomly stratified to diets with either: high dairy protein, moderate CHO (40% CHO: 30% protein: 30% fat; ∼4 dairy servings); high dairy protein, high CHO (55%: 30%: 15%; ∼4 dairy servings); or control (55%: 15%: 30%; ∼1 dairy serving). Energy restriction (500 kcal/day) was achieved through diet (∼250 kcal/day) and EXT (∼250 kcal/day). Body composition was measured using dual‐energy X‐ray absorptiometry before, midway, and upon completion of the intervention. Results: Eighty‐nine (25 M/64 F) of 115 participants completed the 16‐week intervention, losing 7.7 ± 3.2 kg fat mass ( P  < 0.001) and gaining 0.50 ± 1.75 kg lean mass ( P  < 0.01). There was no difference in the changes in body composition (fat mass or lean mass) between groups. Conclusions: Compared to a healthy control diet, energy‐restricted high‐protein diets containing different proportions of fat and CHO confer no advantage to weight loss or change in body composition in the presence of an appropriate exercise stimulus.